DINK phenomenon in Singapore. - Law, Shu Hui. (2009)
DINK Phenomenon in Singapore is a comprehensive 16-page news feature comprising of four sections that examines dual income married couples who are childless by choice (also termed as DINKs, which stands for Double Income No Kids). It is a timely report after Prime Minister Lee Hsien Loong spoke about the low fertility rate in Singapore and delivered measures to combat the problem during his National Day Rally speech in 2008. Through interviews with more than 20 people, we look into why local DINKs choose to be childfree, the pressure they face as a result of their decisions, as well as the tipping points that reversed childfree mindsets for some of them. We conclude that the DINK phenomenon is here to stay, and while Singaporeans might not be ready to embrace DINK couples and their childfree mindsets now, they might become more accepting of them in future.